2021
DOI: 10.1186/s13613-021-00816-6
|View full text |Cite
|
Sign up to set email alerts
|

Ability of procalcitonin to distinguish between bacterial and nonbacterial infection in severe acute exacerbation of chronic obstructive pulmonary syndrome in the ICU

Abstract: Background To assess the ability of procalcitonin (PCT) to distinguish between bacterial and nonbacterial causes of patients with severe acute exacerbation of COPD (AECOPD) admitted to the ICU, we conducted a retrospective analysis of two prospective studies including 375 patients with severe AECOPD with suspected lower respiratory tract infections. PCT levels were sequentially assessed at the time of inclusion, 6 h after and at day 1, using a sensitive immunoassay. The patients were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Nowadays, the place of NIV is well defined in the recommendations for the treatment of AECOPD, with a demonstration of efficiency in survival and a reduction in intubation (12, 30, 31). The proportion of patients treated with NIV in our study (58.87%) and the increase in the use of NIV is in line with the current literature (20, 26, 32, 33). NIV failure rates (19.2%) were also similar to those reported in the literature (3, 26, 34), the gradual reduction in NIV failure probably reflecting the learning curve and a better selection of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nowadays, the place of NIV is well defined in the recommendations for the treatment of AECOPD, with a demonstration of efficiency in survival and a reduction in intubation (12, 30, 31). The proportion of patients treated with NIV in our study (58.87%) and the increase in the use of NIV is in line with the current literature (20, 26, 32, 33). NIV failure rates (19.2%) were also similar to those reported in the literature (3, 26, 34), the gradual reduction in NIV failure probably reflecting the learning curve and a better selection of patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, the systematic prescription of antibiotics remains controversial, as stated in the latest GOLD recommendations (1). For the ICU population, there is no clear recommendation for antibiotic use (19), and no validated biomarkers have been established to guide prescription (20, 21). Again, previous studies have frequently excluded patients in the ICU (22, 23).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used clinical infection markers, such as PCT and CRP, have certain limitations in the diagnosis of infection. The study showed that PCT has poor accuracy in distinguishing bacterial from nonbacterial infections, and PCT may not be an independent marker for the initiation of antibiotic therapy (16). CRP is often elevated in rheumatic connective tissue diseases.…”
Section: Discussionmentioning
confidence: 93%
“…New tools such as multiplex polymerase chain reaction assay panel (mPCR) can provide bacterial or viral documentation with acceptable sensitivity and specificity in less than six hours [ 33 ], and could help eABT decision-making. However, the impact of PCT in the specific setting of ICU patients with AECOPD remains unclear when opposed to short-course antibiotic therapy with immediate cessation in case of negative bacterial samples [ 17 ]. In the absence of evident bacterial infection, early antibiotic treatment may prove potentially futile or even deleterious, in relation with treatment adverse events or MDR pathogen selection, which may in turn, be associated with prolonged ICU and hospital stays and worse clinical outcome [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an era of antibiotic sparing, the relevance of systematic antibiotic therapy may be questioned [11,12], especially since it may promote bacterial colonization and multidrug resistant pathogens selection [13]. The use of biomarker-based strategies has been proposed [14][15][16], but a recent randomized controlled trial failed to demonstrate non-inferiority of a procalcitonin (PCT)-based algorithm to guide initial antibiotic therapy in ICU patients with AECOPD [17]. Hence, national and international guidelines still recommend systematic antibiotic use as soon as mechanical ventilation is required in ICU patients with AECOPD [1,18].…”
Section: Introductionmentioning
confidence: 99%